Vikela Ekhaya: A Novel, Community-based, Tuberculosis Contact Management Program in a High Burden Setting. (24th July 2021) - Kay, Alexander W; Sandoval, Micaela; Mtetwa, Godwin; Mkhabela, Musa; Ndlovu, Banele; Devezin, Tara; Sikhondze, Welile; Vambe, Debrah; Sibanda, Joyce; Dube, Gloria S; Stevens, Robert H; Lukhele, Bhekumusa; et al.
Abstract: Background: The prevention of tuberculosis (TB) in child contacts of TB cases and people living with human immunodeficiency virus (HIV) is a public health priority, but global access to TB preventive therapy (TPT) remains low. In 2019, we implemented Vikela Ekhaya, a novel community-based TB contact management program in Eswatini designed to reduce barriers to accessing TPT. Methods: Vikela Ekhaya offered differentiated TB and HIV testing for household contacts of TB cases by using mobile contact management teams to screen contacts, assess their TPT eligibility, and initiate and monitor TPT adherence in participants' homes. Results: In total, 945 contacts from 244 households were screened for TB symptoms; 72 (8%) contacts reported TB symptoms, and 5 contacts (0.5%) were diagnosed with prevalent TB. A total of 322 of 330 (98%) eligible asymptomatic household contacts initiated TPT. Of 322 contacts initiating TPT, 248 children initiated 3 months of isoniazid and rifampicin and 74 children and adults living with HIV initiated 6 months of isoniazid; 298 (93%) completed TPT. In clustered logistic regression analyses, unknown HIV status (adjusted odds ratio [aOR] 5.7, P  = .023), positive HIV status (aOR 21.1, P  = .001), urban setting (aOR 5.6, P  = .006), and low income (aOR 5.9, P  = .001) predicted loss from the cascade of care among TPT-eligible contacts. Conclusion: Vikela Ekhaya demonstrated that community-based TB household contact management is a feasible, acceptable, and successful strategy for TB screening and TPT delivery. The results of this study support the development of novel, differentiated, community-based interventions for TB prevention and control. Abstract : Vikela Ekhaya offered differentiated tuberculosis and human immunodeficiency virus testing for 945 household contacts of 244 tuberculosis cases, using mobile contact management teams to screen contacts, and initiating and monitoring tuberculosis preventive therapy (TPT) adherence for 322 contacts in their homes. The program achieved TPT initiation rates of 98% and completion rates of 93% using community-based service delivery.